Implementasi Pelaksanaan Administrasi Perceraian Secara Elektronik Melalui E-Court Dalam Upaya Peningkatan Pelayanan Publik Di Pengadilan Agama Pekanbaru Kelas 1A - Hayatina, Nursri; Pivit Septiary Chandra (PESIRAH: Jurnal Administrasi Publik, 2023)
The Pekanbaru Class 1A Religious Court is a judicial body under the auspices of the Supreme Court which has carried out the implementation of electronic divorce administration "E-Court" which is a form of transformation from manual administration to electronic-based administration in accordance with PERMA (Supreme Court Regulation) Number 1 of 2019 which states that it aims to create justice that saves time, cost and energy for parties and advocates and makes the judiciary more transparent, effective and efficient. The purpose of this study is to find out how the implementation of divorce administration electronically through E-Court and to find out what are the obstacles in its implementation. This study used qualitative descriptive method and collected data through interviews, observation and documentation. The data processing technique that researchers use is a data analysis technique. This research uses one variable in its operational concept which is guided by Edward's theory which is the source of problems and prerequisites for successful policy implementation, namely Communication, Resources, Disposition and Bureaucratic Structure. The results showed that the implementation of electronic divorce administration through E-Court at the Pekanbaru Religious Court can be said to run as it should and can improve public services. However, there are still a few obstacles such as server problems from the Supreme Court, network problems and lack of user understanding, namely the elderly in conducting divorce administration electronically through E-Court. Keywords: Implementation, Divorce Administration, E-Court